Transarterial chemoembolization for hepatocellular carcinoma: Treatment algorithm proposed by Chinese College of Interventionalists (CCI) - Hai-Dong Zhu; Rong Liu; Zhong-Zhi Jia; Dong-Dong Xia; Bin-Yan Zhong; Wen-Zhe Fan; Jian Lu; Ming Zhao; Gao-Jun Teng (EngMedicine)
Transarterial chemoembolization (TACE) is one of the most commonly used local treatments for hepatocellular carcinoma (HCC). Experts from the Chinese College of Interventionalists proposed a treatment algorithm regarding the use of TACE for the treatment of HCC in the context of the pathogenesis and biological behavior of HCC, incidence of concurrent hepatitis virus infection or liver cirrhosis, patient characteristics, and potential adverse reactions to treatment. The goal of this algorithm is to further standardize the practice of the TACE procedure based on the updated global evidence on HCC research and clinical experience from Chinese interventional radiologists.